Qualidade do leite, saúde da glândula mamária, padrões fisiológicos e comportamentais de vacas lactantes, em sistema compost barn no semiárido - Cruz, Suelange Oliveira (2025)
The objective of this study was to evaluate milk production and quality, mammary gland health status, thermal environment, bedding conditions, locomotion, physiological parameters, behavior and temperament of lactating dairy cows managed in a compost barn confinement system during the dry and rainy seasons in a semi-arid region. The study was carried out on a commercial farm in the municipality of Nossa Senhora da Glória, in the Alto Sertão region of Sergipe, using 30 Girolando cows. The variables analyzed included the thermal characterization of the environment, milk production and composition, somatic cell count (SCC), standard plate count (SPC), milk acidity, occurrence of mastitis, hock and udder hygiene, teat hyperkeratosis, as well as physiological, behavioral, lameness, bedding quality and thermal comfort indices. The results indicated that the time of year significantly influenced milk production and some parameters of milk quality, litter quality, and physiological and behavioral parameters. However, no significant differences were observed in the somatic cell count, standard plate count, animal hygiene conditions, occurrence of mastitis, teat hyperkeratosis, and lameness. Thus, it is concluded that the time of year influences physiological and behavioral aspects as well as some parameters of milk quality of lactating cows in a compost barn system.